Numerical assessment of dielectrically-modulated short- double-gate PNPN TFET-based label-free biosensor. (March 2023) - Baruah, Karabi; Baishya, Srimanta
Abstract: A comprehensive investigation of dielectrically modulated Ge-source short double-gate PNPN tunnel FET (SG-PNPN TFET) based label-free biosensor is presented. Short gates and counter-doped pockets in the SG-PNPN TFET architecture improve band-to-band tunneling, which subsequently raises the device's drain current sensitivity. On the source side of the device, a nanocavity is created between the gate and the SiO2 layer. The sensing performance of the device was evaluated using the effect of the dielectric constant and charge density of the biomolecules. The non-ideal performance of the biosensor can be understood by analyzing the consequences of steric hindrance and irregular probe placement. The concave profile has the highest value of sensitivity among all the non-uniform profiles considered (including ascending, descending, concave, and convex). The sensitivity comparison of the proposed TFET biosensor with other FET-based biosensors revealed that the SG-PNPN TFET could function admirably as a low-power biosensor with improved sensitivity.